Perdas quantitativas na colheita mecanizada de soja em diferentes condições operacionais de duas colhedoras - Magalhães, Stefânia Caixeta [UNESP]; Oliveira, Beatriz Costa; Toledo, Anderson [UNESP]; Tabile, Rubens Andre [UNESP]; Silva, Rouverson Pereira [UNESP] (My University, 2009)
Mechanized harvesting losses are one of the main problems in the soybean production. This work aimed characterize the quantitative losses of productivity for area, in the mechanized harvesting system in commercial production soybean grains, in function of harvesting displacement speed and year of production. The test was accomplished using a randomized design in a fatorial scheme 2x2, being treatments composed by two harvesting operating in two speeds, 4,0 a 4,5 km h-i and 6,0 a 7,0 km h-i, with five replications for each treatment. The harvesting used Massey Ferguson 5650 Advanced, year of production 2003 e Massey Ferguson 5650 Advanced, year of production 2004. They were evaluated the soybean grains losses caused by the cleaning and separation systems, cut deficiency in the harvesting cutterhead and total losses. The results showed the losses of systems of separation was influenced by harvesting, and the others variables are not significative alterations and the losses in the systems of cleaning showed more contribution for the total losses.
Quantitative losses in the soybean mechanized harvesting in different operational conditions of two harvesters
Keywords: Glycine max; Harvesting; Speed